(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Background: Persistent respiratory disorders place a heavy strain on individuals and healthcare systems because they frequently lead to repeated hospital admissions and extended hospitalizations. For people with long-term respiratory disorders, chest physical therapy (CPT) is a popular strategy to enhance respiratory function and manage symptoms. Optimizing patient care and resource allocation in healthcare settings requires an understanding of how well CPT reduces chronic patient hospital stays.The aim of this research is to evaluate the effectiveness of chest physical therapy in improving quality of life and reducing chronic patient hospital stay. Method: To classify necessary research published between 2018 and 2022, a comprehensive search of databases, including Scopus, PsycINFO, MEDLINE and Web of Science, was done. The inclusion criteria for this study were studies written in English that specifically studied effectiveness of chest physical therapy in improving quality of life and reducing chronic patient hospital stay, the studies chosen had to use well-established scales for measurement and provide valuable data on team dynamics. Eleven studies were included in the synthesis after initial screening and quality assessment. Results: The study found that chest physical therapy (CPT) significantly reduces hospital stays for individuals with chronic respiratory conditions. It also improves respiratory function and symptom management. However, the effectiveness of CPT depends on adherence to treatment protocols and individual patient characteristics. The study emphasizes the importance of tailored treatment approaches in managing respiratory care. Overall, these findings offer valuable insights into CPT’s role in reducing hospital stays and improving outcomes. Conclusion: This systematic review on respiratory health management provides insights into its multifaceted nature, identifying themes, suggesting future research, and highlighting limitations. Recommendations include expanding research, addressing healthcare disparities, fostering collaboration, embracing technology, and advocating for policy changes.